2016
DOI: 10.2334/josnusd.16-0278
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β, TNF-α, and IL-6 levels in gingival fluid and serum of patients with ischemic stroke

Abstract: It has been documented that an increaseof immune cells in periodontitis may stimulate the process of atherosclerosis and lead to ischemic stroke. The aim of this study was to investigate whether there is any significant difference in serum and gingival crevicular fluid (GCF) cytokine concentrations between patients with early ischemic stroke (IS) and a control group. Eighty-six patients were consecutively enrolled for this study, 50 with ischemic stroke and 36 as a control group with no previous stroke. Only d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 28 publications
4
26
0
2
Order By: Relevance
“…Other studies also found correlations between the local and the general markers verifying our suggestion for the link between them (Noack et al, ; Zheng, Chen, Shi, Jepsen, & Eberhard, ). There is still, though, great variety in the results in the literature with other studies failing to prove association between GCF and blood biomarkers (Fell et al, ; Fiorini et al, ; Wytrykowska et al, ). Different methodologies, characteristics of the groups, and various selection criteria can justify this great diversity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies also found correlations between the local and the general markers verifying our suggestion for the link between them (Noack et al, ; Zheng, Chen, Shi, Jepsen, & Eberhard, ). There is still, though, great variety in the results in the literature with other studies failing to prove association between GCF and blood biomarkers (Fell et al, ; Fiorini et al, ; Wytrykowska et al, ). Different methodologies, characteristics of the groups, and various selection criteria can justify this great diversity.…”
Section: Discussionmentioning
confidence: 98%
“…All of them were found higher in the periodontitis groups compared with healthy ones, in both serum and GCF; visfatin, VEGF, oncostatin M, and TNF‐α decreased, in both fluids, after scaling and root planning (Baltacioglu, Akalin, Alver, Deger, & Karabulut, ; Gokul, Faizuddin, & Pradeep, ; Pradeep et al, ; Pradeep, Prapulla, Sharma, & Sujatha, ; Raghavendra et al, ; Thorat, Pradeep, & Garg, ; Turer, Durmus, Balli, & Guven, ). In another study that investigated patients with ischemic stroke, the authors found higher concentrations of some cytokines in the serum in the ischemic patients' group but no correlation between the GCF concentrations and the serum ones (Wytrykowska, Prosba‐Mackiewicz, & Nyka, ). The same results, with no association in serum and GCF, though there were higher concentrations in GCF of periodontitis patients, were also reported for different cytokines in a cohort of pregnant women (Fiorini et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have also shown that IL-6 is involved in the inflammatory response during cerebral ischemia. The detection of IL-6 in patients with acute cerebral infarction found that IL-6 in the cerebrospinal fluid and serum is an independent predictor of cerebral infarction: the greater the volume of cerebral infarction, the higher the level of IL-6, and this was not related to the location of the cerebral infarction (Wytrykowska et al, 2016). IL-6 increases vascular endothelial cell monolayer permeability in vitro, and contributes to ischemia-related bloodbrain barrier dysfunction.…”
Section: Il-6mentioning
confidence: 99%
“…Таким образом, нами в динамике обследования пациентов, страдающих ишемическим инсультом выявлено повышение уровня фактора некроза опухоли-альфа при поступлении и достоверные корреляционные зависимости изменения его уровня в динамике терапии в течение 14 дней наблюдения за пациентами. Несмотря на противоречивость данных литературы, не каждый из источников которой свидетельствует о достоверном изменении концентрации TNFα [29,41], наши данные свидетельствуют о существенном увеличении уровня данного цитокина в сыворотке крови в среднем у наблюдаемых нами лиц. Правда, при этом довольно существенный процент лиц имел показатели TNFα (около 20-24%) в пределах < 10 пг/мл.…”
Section: результаты и обсуждениеunclassified
“…Вместе с тем существуют противоречивые данные об уровнях TNFα в сыворотке и плазме крови при остром ишемическом инсульте. Некоторые исследования показали, что уровни TNFα остаются неизменными после инсульта, в то время как другие сообщают о повышенных уровнях цитокина, хотя и с разными пиковыми периодами [10,25,41].…”
unclassified